2018
DOI: 10.1002/brb3.1007
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to attachment narratives dynamically modulates cortical arousal during the resting state in the listener

Abstract: BackgroundAffective stimulation entails changes in brain network patterns at rest, but it is unknown whether exogenous emotional stimulation has a prolonged effect on the temporal dynamics of endogenous cortical arousal. We therefore investigated differences in cortical arousal in the listener following stimulation with different attachment‐related narratives.MethodsResting‐state EEG was recorded from sixteen healthy subjects for ten minutes each with eyes closed: first at baseline and then after passively lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Listening to a patient’s story about a dismissive parental relationship in childhood reduced supplementary motor areas’ connectivity with other areas of the brain during subsequent rest ( Borchardt et al, 2015 ). In another study, reduced functional connectivity patterns were identified between the caudate nucleus, TPJ, DLPFC, and cingulate cortex after certain types of emotional attachment narrative ( Krause et al, 2018 ), and EEG findings suggest that, while subjects remain aroused after hearing attachment narratives, they affectively disengage from content about dismissiveness soon after hearing it ( Borchardt et al, 2018 ). Finally, negative emotions induced by movie clips inhibited lateral prefrontal cortical activation during a subsequent theory-of-mind (ToM) task in a functional near-infrared spectroscopy study ( Himichi et al, 2015 ); due to the method used in this study only the activity of lateral prefrontal cortex was measured.…”
Section: Feature Films In Non-invasive Neuroimaging Studies Of Emotiomentioning
confidence: 99%
“…Listening to a patient’s story about a dismissive parental relationship in childhood reduced supplementary motor areas’ connectivity with other areas of the brain during subsequent rest ( Borchardt et al, 2015 ). In another study, reduced functional connectivity patterns were identified between the caudate nucleus, TPJ, DLPFC, and cingulate cortex after certain types of emotional attachment narrative ( Krause et al, 2018 ), and EEG findings suggest that, while subjects remain aroused after hearing attachment narratives, they affectively disengage from content about dismissiveness soon after hearing it ( Borchardt et al, 2018 ). Finally, negative emotions induced by movie clips inhibited lateral prefrontal cortical activation during a subsequent theory-of-mind (ToM) task in a functional near-infrared spectroscopy study ( Himichi et al, 2015 ); due to the method used in this study only the activity of lateral prefrontal cortex was measured.…”
Section: Feature Films In Non-invasive Neuroimaging Studies Of Emotiomentioning
confidence: 99%
“…Functional connectivity changes were also reported after emotional narratives and movies (van Marle et al, 2010 ; Borchardt et al, 2015 ). EEG findings have suggested that subjects remain aroused after emotional narratives (Borchardt et al, 2018 ). Finally, negative emotions induced by movie clips inhibited lateral prefrontal cortical activation during a subsequent theory of mind task (Himichi et al, 2015 ).…”
Section: Emotional Valence and Arousal During Narratives Differentialmentioning
confidence: 99%
“…Departing from this background, if attachment influences the development of the self, the constitution, and the differentiation of the self and others and is considered closely linked to SR processing (Brockman, 2002 ; Northoff, 2011 ), we may expect an impact on the spontaneous/resting state activity of the brain, as suggested by a study showing a relation between increased measures of individual negative childhood experiences and a more entropic neuronal activity in medial prefrontal cortex during rest (Duncan et al, 2015 ; see Figure 1 ). Moreover, research on the resting state fMRI showed that emotional processing of attachment-related content induces carryover effects and alters the brain network configurations at rest (Krause et al, 2016 , 2018 ; Borchardt et al, 2018 ).…”
Section: Early Relational Experiences Attachment and The Developmentmentioning
confidence: 99%